IS THE AGREEMENT WITH FINTECH SERVICES VALID? - Merlin Swantamalo Magna (Surakarta Law and Society Journal, 2020)
The industrial revolution 4.0 was marked by the birth of economic globalization supported by significant technological developments. Rapid progress is evidenced by the increasingly diverse creative and innovative business ideas, which are in the financial sector. Financial institutions in Indonesia are also increasingly developing along with the economic growth rate, which can be seen with a variety of variations of financial instruments circulating in the community, both in the banking sector and in the non-banking sector. One of them is the emergence of Financial Technology that makes it easy for the public to conduct banking activities. The facilities offered are not without problems, because they need a legal umbrella as an effort to provide legal certainty to be able to support a conducive business climate. This paper tries to analyze the validity of the agreement that occurs when using various fintech services in Indonesia. Keywords : Agreement, Civil Code, Financial, Fintech.